How deaf children learn : what parents and teachers need to know - Marschark, Marc; Hauser, Peter C. (New York : Oxford University Press, 2012)
How can parents and teachers most effectively support the language development and academic success of deaf and hard-of-hearing children? Will using sign language interfere with learning spoken language? Should deaf children be placed in classrooms with hearing children? Are traditional methods of teaching subjects such as reading and math to hearing children appropriate for deaf learners? As many parents and teachers will attest, questions like these have no easy answers, and it can be difficult for caring adults to separate science from politics and fact from opinion in order to make informed decisions about how to help deaf children learn.
What it's all about -- Introduction to deaf children -- On hearing and not hearing -- Language and communication -- Family and peers : foundations of learning -- Deaf cognition -- Learning and memory -- Problem solving and knowledge -- Reading -- Doing math : foundations and outcomes -- The deaf education classroom -- Where do we go from here?.
Includes bibliographical references and index.
Keywords: Deaf children -- Means of communication; Deaf children -- Language; Deaf -- Education; Parents of deaf children